DOES SPIRITUALITY PROMOTE AUTONOMY OR SUBMISSION? - Syafiq, Muhammad (Jurnal Psikologi Teori dan Terapan, 2011)
Studies on spirituality have been conducted extensively in psychology over the last decade. However, the topic has been mostly explored in mental-health setting rather than in other areas in psychology. It is not surprising, then, if the most issues explored in the studies were the impacts orÂ functions of spirituality toward psychological well-being rather than toward the realisation of human potentials. In fact, the main reason why many scientists in psychology propose to study spirituality as a separated construct from religion is its unique characteristic which enable individuals to achieve their personal higher meanings or values. This article aims to examine whether spirituality and spiritual practices promote autonomy as claimed by many scientists. The insights revealed from studies on Eastern spiritualities and Western new age spirituality movement will be employed.